Carnivore use of an avocado orchard in southern California - Borchert, M.; Davis, F. W.; Kreitler, J. (California Fish and Game Journal, 2008)
In southern California avocados are an important commercial fruit that often are planted near or immediately adjacent to wildlands. Among cultivated fruits, avocados are unusually high in both lipids and proteins. Fruits remain green on the tree and ripen only after they fall to the ground or are harvested. As a result, they offer a relatively constant, year-round food source in the form of unharvested, fallen fruit. In 2005 for 5.5 months, we camera-trapped medium and large mammals in 13.5 ha of a 55.5 ha commercial avocado orchard in southern California. We also monitored fruit fall and subsequent removal to quantify the amount of energy available to mammals and estimated how much of the ground fruit they consumed. Cameras captured 7 carnivores: black bear, Ursus americanus, domestic dog, coyote, Canis latrans, bobcat, Lynx rufus, gray fox, Urocyon cinereoargenteus, raccoon, Procyon lotor, and striped skunk, Mephitis mephitis; non-carnivores included western gray squirrel, Sciurus griseus and Virginia opossum, Didelphia virginiana. All but bobcats were photographed eating avocados. Black bears, gray foxes and striped skunks frequented the part of the orchard least affected by human activities. In contrast, coyotes and raccoons were more common where humans and domestic dogs were present. Mammals consumed all or nearly all marked avocados on the ground, usually within 50 days. We estimated that they consumed only a small portion (<2%) of the total fruit crop. Avocado orchards offer super-rich food patches that are readily accessible to an array of medium and large mammals.